Investigation of Energetic Parameters of Oscillating Synchronous Pulsating Current Motors - Urmoniene, L.; Gecys, S.; Guseinoviene, E.; Cirtautas, V. (Elektronika ir Elektrotechnika, 2011)
This paper deals with oscillating linear synchronous pulsating current motor compressor drive supplied by sinusoidal and rectangular voltage. While creating mathematical model of the motor for investigation, Matlab software was used for solving of differential equations. Modeling results while supplying motor by sinusoidal and rectangular voltage and changing firing angle a of thyristor, frequency of voltage f and a load R. Characteristics and energetic parameters of oscillating linear pulsating current motor were obtained and analyzed. Ill. 10, bibl. 6, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.278